Mn2Sb-based alloy single crystal and preparation method and application thereof
Through melt cooling method and fine temperature control program, the problem of heterophasic phase generation in single crystals of Mn2Sb-based alloy was solved, and high-quality single crystal materials were prepared, suitable for magnetic refrigeration, magnetic storage, magnetic sensing and other fields, improving the Material properties and scope of application.
Patent Information
- Application Number
- CN202411295017.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
The prior art is difficult to prepare high-quality Mn2Sb-based alloy single crystals. There is a 1:1 hexagonal structure of MnSb heterophases in polycrystals and single crystals, which affects magnetic properties and thermal stability of materials, limiting their magnetic refrigeration and magnetic storage. Applications in fields such as magnetic sensing.
The melt cooling method is adopted to ensure the high purity of the metal raw materials by precisely controlling the alloy composition and temperature control procedures, and clean them with inert gas. Heating them with a well furnace, oscillation and cooling and quenching to avoid miscellaneous phase generation and prepare them for free. Mn2Sb-based alloy single crystal with high quality and large size.
The Mn2Sb-based alloy single crystal is successfully prepared without hexagram, high quality and good integrity, which is suitable for higher requirements of magnetic refrigeration, magnetic storage, magnetic sensing and other fields, improving the overall performance and service life of the material.
Smart Images

Figure CN119145034A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic functional single crystal growth, and in particular to a Mn2Sb-based alloy single crystal and a preparation method and application thereof. Background Art
[0002] Mn2Sb-based alloy is a magnetic functional crystal with unit cell parameters of a=4.1048 angstroms, c=6.4770 angstroms, space group P4 / nmm, and Cu2Sb-type tetragonal structure. Pure Mn2Sb alloy belongs to ferrimagnetic structure. Below 550K, the inequivalent Mn magnetic sublattice MnI and MnII are arranged antiparallel along the c-axis direction, showing ferrimagnetism. As the temperature decreases, below 240K, MnI and MnII turn to the ab plane and undergo spin reorientation. By element substitution, a phase transition from ferrimagnetic to antiferromagnetic state induced by temperature or magnetic field can be obtained in Mn2Sb-based alloy. As the Mn site is replaced by transition elements, a rich magnetic phase transition is presented, showing novel transport phenomena such as topological Hall effect, which may be related to its possible topological magnetic structure. However, the Mn2Sb-based alloy polycrystals and single crystals prepared by the arc melting method and the Bridgman method reported so far both contain a 1:1 hexagonal MnSb impurity phase, which cannot meet the scientific research and practical application of Mn2Sb-based alloy single crystals in multiple fields such as magnetic refrigeration, magnetic storage, and magnetic sensing.
[0003] Therefore, there is an urgent need to develop a Mn2Sb-based alloy single crystal and a preparation method thereof to obtain high-quality single crystal materials. Summary of the invention
[0004] In view of this, the present invention provides a Mn2Sb-based alloy single crystal and a preparation method and application thereof, so as to obtain a high-quality Mn2Sb-based alloy single crystal without impurities and applicable to the fields of magnetic refrigeration, magnetic storage, magnetic sensing, etc. with higher requirements.
[0005] In a first aspect, the present invention provides a method for preparing a Mn2Sb-based alloy single crystal, the method comprising the following steps:
[0006] S1. Weighing
[0007] Weigh the metal element according to the stoichiometric ratio and place it in the corundum crucible a;
[0008] S2. Sealing the tube
[0009] The corundum crucible a in step S1 is placed in a quartz tube, and the quartz tube is cleaned with an inert gas, evacuated, and sealed;
[0010] S3. Smelting
[0011] The quartz tube sealed in step S2 is placed vertically in the corundum crucible b, heated until the metal element is melted, and kept warm;
[0012] S4, Oscillation cooling
[0013] The corundum crucible b kept warm in the oscillation step S3 is subjected to a process of cooling-heating-cooling in sequence at a certain rate until crystal nuclei are precipitated in the melt;
[0014] S5. Cooling
[0015] Cooling the corundum crucible b after the temperature reduction in step S4 to a final temperature at a certain rate;
[0016] S6, Quenching
[0017] At the final temperature of step S5, the quartz tube is taken out and rapidly quenched to obtain a Mn2Sb-based alloy single crystal.
[0018] Based on the above basic steps, the inventors made further optimizations, including:
[0019] In step S1, when weighing the metal element, the inventors took into account that metal manganese Mn would volatilize to a certain extent under high temperature conditions, and therefore designed that Mn could be moderately excessive by 3%, which is beneficial for the manganese content in the final product to still reach the expected standard.
[0020] In step S2, the inventors use inert gas, including but not limited to argon, to clean the air, water vapor, etc. in the quartz tube. After multiple vacuum pumping, they will consider whether to fill the quartz tube with inert gas based on actual conditions to reduce the possible oxidation problem of raw materials in the later stage, thereby avoiding the formation of impurities.
[0021] In step S3, a pit furnace or a box furnace is selected as the heating chamber, which has a large capacity and is easy and safe to operate.
[0022] By adopting the above technical scheme, Mn2Sb-based alloy single crystals with no impurities, high quality, good integrity and large size can be successfully prepared; and the preparation steps are simple, the operation is safe, the growth cycle is short and the success rate is high.
[0023] Furthermore, in step S1, the purity of the metal element is not less than 99.9%.
[0024] Furthermore, in step S3, the insulation time is 24 to 48 hours.
[0025] Furthermore, in step S3, the insulation temperature is 1010°C.
[0026] Furthermore, in step S4, the oscillation times are 2 to 3 times, the cooling rate is 1°C / h to 2°C / h, and the heating rate is 1°C / h to 3°C / h.
[0027] By adopting the above technical solution, it is possible to melt away excess crystal nuclei, reduce the number of nuclei, and avoid obtaining a large amount of fine crystal materials.
[0028] Furthermore, the crystal nucleus precipitation temperature is 950°C.
[0029] By adopting the above technical solution, crystal nuclei can be precipitated in a supersaturated high-temperature melt.
[0030] If the temperature is higher than 950℃, nucleation may be inhibited, because higher temperature means that the liquid state is more stable, the thermal motion of atoms or molecules is stronger, which is not conducive to the formation of an ordered crystal structure; in addition, if the temperature is very high, any crystal nuclei that have been formed may also dissolve back into the liquid phase, because the high temperature provides enough energy to destroy the crystal structure. If the temperature is lower than 860℃, a 1:1 hexagonal MnSb phase hybrid phase in the low temperature region will be generated.
[0031] Furthermore, in step S5, the cooling rate is 1°C / h to 2°C / h.
[0032] By adopting the above technical solution, a small number of single crystal materials with larger sizes can be formed.
[0033] Further, the temperature is cooled to 860°C.
[0034] If the cooling temperature is higher than this, any existing 1:1 phase may be dissolved or unstable; conversely, if the temperature is lower than this, new phases may precipitate, causing changes in the material's microstructure.
[0035] Furthermore, in step S6, the quenching medium is ice water or liquid nitrogen.
[0036] By adopting the above technical solution, the high-temperature 2:1 tetragonal Mn2Sb high-temperature phase can be maintained, and the generation of the 1:1 hexagonal MnSb phase impurity in the low-temperature zone can be avoided.
[0037] In a second aspect, the present invention provides a Mn2Sb-based alloy single crystal prepared by the above method, wherein the chemical formula of the Mn2Sb-based alloy single crystal is:
[0038] Mn 2-x T x Sb(Ⅰ);
[0039] In formula (I), the value range of x is 0≤x≤1, and T is a transition metal.
[0040] In a third aspect, the present invention relates to the application of the Mn2Sb-based alloy single crystal prepared by the above method in the fields of magnetic refrigeration, magnetic storage and magnetic sensing.
[0041] The Mn2Sb-based alloy single crystal provided by the present invention has the following beneficial effects compared with the prior art:
[0042] 1. The method for preparing Mn2Sb-based alloy single crystals of the present invention has simple steps, short growth cycle, high success rate, and the obtained single crystals are free of impurities, high quality, good integrity, and large size, and are suitable for most conventional research methods. At the same time, it also effectively avoids the problem of impurities existing in the prior art when preparing Mn2Sb-based alloy single crystals.
[0043] 2. The Mn2Sb-based alloy single crystal of the present invention can be widely used in multiple fields with higher requirements such as magnetic refrigeration, magnetic storage, magnetic sensing, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 The Mn prepared in Example 1 of the present invention 1.9 Co 0.1 The effect diagram of Sb single crystal; in the figure, (a) is Mn 1.9 Co 0.1 XRD diffraction pattern of Sb single crystal, (b) is Mn 1.9 Co 0.1 The actual image obtained by repeating the experiment twice for Sb single crystal, (c) is Mn 1.9 Co 0.1 Laue diffraction pattern of Sb single crystal, (d) is Mn 1.9 Co 0.1 Standard Laue diffraction spot pattern of Sb single crystal;
[0046] Figure 2 The Mn prepared in Example 1 of the present invention 1.9 Co 0.1 XRD diffraction pattern of Sb polycrystal;
[0047] Figure 3 Mn prepared in Comparative Example 2 of the present invention 1.9 Co 0.1 The effect diagram of Sb alloy material; in the figure, (a) is Mn 1.9 Co 0.1 XRD diffraction pattern and physical image of Sb single crystal, (b) is Mn 1.9 Co 0.1 XRD diffraction pattern of Sb polycrystal;
[0048] Figure 4 The Mn prepared in Example 2 of the present invention 1.8 Co 0.2 The polycrystalline XRD diffraction pattern corresponding to the Sb single crystal;
[0049] Figure 5 The Mn prepared in Example 3 of the present invention 1.9 Ni 0.1 XRD diffraction pattern of polycrystalline Sb single crystal. DETAILED DESCRIPTION
[0050] As a material with special magnetic and thermodynamic properties, Mn2Sb-based alloys are widely used in many fields such as magnetic refrigeration, magnetic storage, magnetic sensing, energy capture and exchange, spin electronics, brakes and sensors, and have great application value. However, the research and application of Mn2Sb-based alloys are still in their early stages. In the actual application process, some key issues still need to be solved, such as phase change temperature control, hysteresis loss, mechanical properties and production costs. With the continuous advancement of science and technology and the continuous improvement of material performance requirements in related fields, the development and research of Mn2Sb-based alloys still need to be expanded and deepened.
[0051] Prior to this application, the preparation of existing Mn2Sb-based alloys was mostly achieved by arc melting or Bridgman method. Although the arc melting method for preparing Mn2Sb-based alloys has the advantages of simple equipment, convenient operation, low cost and short preparation cycle, due to the high temperature and the effect of the arc, some impurity elements that are difficult to control may be introduced, thereby affecting the purity of the alloy; in addition, due to the large temperature gradient during arc melting, if the cooling rate is not properly controlled, it is easy to cause alloy component segregation and microstructure inhomogeneity. Although the Bridgman method can be used to prepare Mn2Sb-based alloys, high-quality, low-defect and controllable alloy materials can be obtained, the equipment used in this method is complex, the cost is high and the preparation cycle is long, resulting in low production efficiency of the alloy, which is not conducive to large-scale production.
[0052] The inventors of the present application have found in practice that a 1:1 hexagonal MnSb impurity phase exists in both polycrystalline and single crystal materials of Mn2Sb-based alloys prepared by existing methods. The presence of this impurity phase will change the magnetic structure of the Mn2Sb-based alloy, thereby affecting its magnetic properties. In addition, there may be a difference in thermal expansion coefficient between the MnSb impurity phase and the Mn2Sb-based alloy, resulting in internal stress during temperature changes, which ultimately affects the thermal stability of the material, and even causes cracks and phase separation, reducing the overall performance and service life of the material. At the same time, the presence of this impurity phase will also limit the application of Mn2Sb-based alloys in certain fields, such as the field of magnetic refrigeration. Therefore, when further applying Mn2Sb-based alloys to multiple fields such as magnetic refrigeration, magnetic storage, and magnetic sensing, it is crucial to effectively solve a series of technical problems brought about by the impurity phase on the premise of comprehensively considering the advantages of existing technologies.
[0053] In view of the fact that the existing technologies are not as good as the inventor's expectations, the inventor has made the present invention through further experiments and explorations to solve the above technical problems.
[0054] The present invention successfully prepares high-quality Mn2Sb-based alloy single crystal materials for the first time by using a melt cooling method. By precisely controlling the alloy composition, optimizing the smelting process and strictly controlling the temperature, Mn2Sb-based alloys and single crystal materials with no impurities, high quality, good integrity, large size, short growth cycle and simple steps are prepared. In addition, by further adjusting the process flow, including but not limited to: increasing the cooling rate, not performing oscillating cooling operations, etc., high-quality polycrystalline materials can also be obtained.
[0055] The present invention fully considers the problem of avoiding the formation of impurity phases when designing the method for preparing Mn2Sb-based alloy polycrystalline and single crystal materials. To solve this problem, the inventor first starts with the selection of metal raw materials and the precise control of alloy components, controls the purity of the raw materials to more than 99.9%, and weighs the raw materials strictly according to the stoichiometric ratio to ensure that the impurity content in the raw materials is as low as possible, and avoids the introduction of elements or compounds that are easy to form impurity phases, greatly reducing the possibility of impurity phase generation. Secondly, the inventors carry out smelting in an inert gas atmosphere, effectively preventing the oxidation of metal raw materials and impurity contamination caused by air. Finally, the inventors effectively avoided the 1:1 hexagonal structure of MnSb impurity phase in the low temperature zone by precisely controlling the temperature and temperature control program, thereby obtaining high-quality Mn2Sb-based alloy single crystal materials.
[0056] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of the materials mainly involved in the examples are shown in Table 1 below, and the remaining materials not shown are conventional commercial products.
[0058] Table 1 Material source description
[0059] Material Name Model / Specification factory Manganese Mn Purity ≥99.9%, particle size 1~10mm Zhongnuo New Materials Cobalt Purity ≥99.9%, particle size 3*3mm Zhongnuo New Materials Antimony Sb Purity ≥99.9%, particle size 2~6mm Zhongnuo New Materials NickelNi Purity ≥99.9%, particle size 3*3mm Zhongnuo New Materials
[0060] Example 1
[0061] This embodiment provides a method for preparing Mn 1.9 Co 0.1 The method for forming a single crystal of Sb alloy comprises the following steps:
[0062] S1. Weigh Mn, Co, and Sb according to the stoichiometric ratio and place them in a corundum crucible a;
[0063] S2, placing the corundum crucible a in step S1 in a quartz tube with cotton pads at the bottom of the tube, and then cleaning the quartz tube with argon gas, repeating three times, evacuating the tube at least three times, and then sealing the quartz tube;
[0064] S3, vertically place the quartz tube in the corundum crucible b, and heat the whole in a pit furnace. When the temperature rises to 1010°C, the metal element melts, and keep the temperature for 24 hours;
[0065] S4, using an oscillating method, the corundum crucible b kept in step S3 is cooled to 920°C at 2°C / h, then heated to 990°C at 3°C / h, and finally cooled to 950°C at 2°C / h, at which time crystal nuclei are precipitated in the corundum crucible a;
[0066] S5, cooling the melt in the corundum crucible b after cooling in step S4 to 860°C at a rate of 1°C / h;
[0067] S6. Take out the quartz tube at 860°C and quench it in liquid nitrogen to obtain Mn 1.9 Co 0.1 Sb alloy single crystal.
[0068] After two repeated test operations, the Mn 1.9 Co 0.1 Sb alloy single crystal, such as Figure 1 (b) shows the actual picture, Figure 1 (b) It can be seen that the single crystal samples prepared twice in this embodiment have the characteristics of large size, complete appearance and smooth surface, which shows that the single crystals obtained by this preparation technology have high repeatability and good quality.
[0069] The Mn prepared in this example 1.9 Co0.1 After XRD diffraction analysis, the Sb alloy single crystal was obtained as follows Figure 1 (a) Mn 1.9 Co 0.1 The XRD diffraction pattern of Sb single crystal, as shown in Figure (a), shows that there is only a (001) plane network series diffraction peak in the figure, and there are no diffraction peaks in other directions or impurity phases, indicating that the single crystal sample prepared by this method has a flat and bright surface as the (001) plane, and the diffraction peak is narrow and high, indicating that the single crystal has good quality.
[0070] Further characteristic X-ray irradiation was used to obtain the Mn prepared in this embodiment. 1.9 Co 0.1 The Laue diffraction spot pattern (also called white light XRD diffraction spot) of Sb single crystal is as follows: Figure 1 As shown in (c), it can be seen that the spot is clear and presents a four-fold symmetry. Figure 1 (d) Mn fitted by Qlaue software 1.9 Co 0.1 The standard Laue diffraction spots of the Sb(001) surface almost overlap.
[0071] In summary, the method of the present application can be used to prepare high-quality Mn2Sb-based alloy single crystals, and the obtained single crystals are free of impurities, have good integrity, and are large in size.
[0072] The inventors prepared the Mn 1.9 Co 0.1 The Sb alloy single crystal sample was ground in an agate mortar to obtain micron-sized Mn 1.9 Co 0.1 Sb alloy polycrystalline sample. After XRD diffraction analysis, the sample was obtained as follows Figure 2 Mn 1.9 Co 0.1 The XRD diffraction pattern of Sb polycrystal shows that in the polycrystalline sample prepared in this embodiment, only the diffraction peak of the 2:1 Mn2Sb with the space group P4 / nmm tetragonal structure exists, and there is no diffraction peak of the 1:1 hexagonal MnSb impure phase. This indicates that the method of preparing single crystal material in this application can also obtain a polycrystalline material with good quality and no impurity phase after subsequent processing.
[0073] The inventor selected the literature Shengcan Ma, Guang Yu, Chaoxin Qiu, et al. Topological Hall effect associated with spin reorientation transition in tetragonal Mn 1.9 Co 0.1Sbferrimagnet.Journal ofAlloysandCompounds,2022(921):165919. As comparative example 1 of the present application, according to the relevant records of the document, Mn 1.9 Co 0.1 Sb polycrystalline material is prepared by a multi-step synthesis method through the following steps:
[0074] Mn was prepared by arc melting raw materials with a purity greater than 99.99% in a water-cooled copper crucible under high-purity Ar atmosphere. 1.9 Co 0.1 The invention discloses a Mn Sb alloy steel ingot, comprising: quenching the original cast steel ingot in cold water, and then annealing it in a vacuum quartz tube at 800°C for 8 days to obtain a Mn 1.9 Co 0.1 Sb polycrystalline.
[0075] According to the XRD test and its results recorded in the literature, although this method has obtained Mn 1.9 Co 0.1 Sb polycrystalline material, but its XRD diffraction pattern contains diffraction peaks of MnSb and β-MnO2, indicating that the Mn prepared by this method 1.9 Co 0.1 Sb polycrystalline material is not pure phase, and Mn cannot be obtained by this method. 1.9 C o0.1 Sb single crystal sample.
[0076] In addition, this method first uses an expensive vacuum arc melting furnace to prepare alloy steel ingots, and then uses a vacuum tube annealing method, which can only obtain polycrystalline materials, but they are not pure phases. On the contrary, this application uses a melt cooling method to prepare pure phase single crystal samples in a common pit furnace. The operation is simple, and the preparation method has simple steps, low cost, and high success rate. The prepared single crystal material has no impurity phase, high single crystal quality, good integrity, and large size. It is suitable for most conventional research methods and fills the gap in the preparation of impurity-free Mn2Sb-based alloy single crystals.
[0077] During the experimental investigation, the inventors designed comparative example 2 of the present application by changing some conditions, such as the heating rate during the oscillation process.
[0078] Comparative Example 2
[0079] This comparative example provides a method for preparing Mn 1.9 Co 0.1 The method for forming a single crystal of Sb alloy comprises the following steps:
[0080] S1. Weigh Mn, Co, and Sb according to the stoichiometric ratio and place them in a corundum crucible a;
[0081] S2, placing the corundum crucible a in step S1 in a quartz tube with cotton pads at the bottom of the tube, and then cleaning the quartz tube with argon gas, repeating three times, evacuating at least three times, and then sealing the quartz tube;
[0082] S3, vertically place the quartz tube in the corundum crucible b, and heat the whole in a pit furnace. When the temperature rises to 1010°C, the metal element melts and the temperature is kept for 24 hours;
[0083] S4, using an oscillating method, the corundum crucible b kept in step S3 is cooled to 920°C at 2°C / h, then heated to 990°C at 1°C / min, and finally cooled to 950°C at 2°C / h, at which time crystal nuclei are precipitated in the corundum crucible a;
[0084] S5, cooling the melt in the corundum crucible b after cooling in step S4 to 860°C at a rate of 1°C / h;
[0085] S6. Take out the quartz tube at 860°C and quench it in liquid nitrogen to obtain Mn 1.9 Co 0.1 Sb alloy single crystal.
[0086] like Figure 3 As shown in the picture (a), the Mn prepared in this comparative example 1.9 Co 0.1 Sb single crystal is fine and irregular grains. After XRD diffraction analysis, the following is obtained: Figure 3 (a) Mn 1.9 Co 0.1 The XRD diffraction pattern of Sb single crystal shows that only some diffraction peaks exist and the half-peak width is relatively wide. After further grinding the single crystal material, the following is obtained: Figure 3 (b) The pure phase of Mn 1.9 Co 0.1 Sb polycrystalline XRD diffraction pattern.
[0087] Combining the performance test results of Example 1 and Comparative Example 2, it can be seen that during the oscillation process, the heating rate will affect the nucleation process. A fast heating rate is not conducive to reducing the number of crystal nuclei, and will affect the size and quality of the single crystal, increase the generation of defects, but will not affect the formation of a 2:1 tetragonal structure Mn2Sb high-temperature phase. On the contrary, a slow heating rate means that the system stays in a supercooled state for a longer time, which may lead to the formation of more nucleation centers, and long-term supercooling may lead to the appearance of more metastable phases. Based on this, the inventors believe that under the temperature control and temperature conditions of the present invention, a single crystal material with no impurities, high quality, good integrity and large size can be obtained. Changing any of the conditions will most likely have a greater impact on the final performance of the product.
[0088] Based on the single crystal material prepared in Example 1 that meets the inventor's expectations, the inventor also conducted experiments with different proportions and different metal substitution elements according to the above steps, and provided Examples 2 and 3.
[0089] Example 2
[0090] This embodiment provides a method for preparing Mn 1.8 Co 0.2 The method for forming a single crystal of Sb alloy comprises the following steps:
[0091] S1. Weigh Mn, Co, and Sb according to the stoichiometric ratio and place them in a corundum crucible a;
[0092] S2, placing the corundum crucible a in step S1 in a quartz tube with cotton pads at the bottom of the tube, and then cleaning the quartz tube with argon gas, repeating three times, evacuating the tube at least three times, and then sealing the quartz tube;
[0093] S3, vertically place the quartz tube in the corundum crucible b, and heat the whole in a pit furnace. When the temperature rises to 1010°C, the metal element melts, and keep the temperature for 36 hours;
[0094] S4, using an oscillating method, the corundum crucible b kept in step S3 is cooled to 920°C at 1°C / h, then heated to 990°C at 2°C / h, and finally cooled to 950°C at 2°C / h, at which time crystal nuclei are precipitated in the corundum crucible a;
[0095] S5, cooling the melt in the corundum crucible b after cooling in step S4 to 860°C at a rate of 2°C / h;
[0096] S6. Take out the quartz tube at 860℃ and quench it in ice water to obtain Mn 1.8 Co 0.2 Sb alloy single crystal.
[0097] The Mn prepared in this example 1.8 Co 0.2 The Sb alloy single crystal sample was ground in an agate mortar and analyzed by XRD diffraction to obtain Mn 1.8 Co 0.2 Sb polycrystalline XRD diffraction pattern, such as Figure 4 As shown in the figure, the Mn prepared in this embodiment 1.8 Co 0.2 The polycrystalline material after grinding the Sb alloy single crystal material is pure phase. Since the polycrystalline material is ground from the single crystal, it can be inferred that the Mn 1.8 Co 0.2 The Sb alloy single crystal material is also a pure phase tetragonal structure crystal.
[0098] Example 3
[0099] This embodiment provides a method for preparing Mn 1.9 Ni 0.1 The method for forming a single crystal of Sb alloy comprises the following steps:
[0100] S1. Weigh Mn, Ni and Sb according to the stoichiometric ratio and place them in a corundum crucible a;
[0101] S2, placing the corundum crucible a in step S1 in a quartz tube with cotton pads at the bottom of the tube, and then cleaning the quartz tube with argon gas, repeating three times, evacuating the tube at least three times, and then sealing the quartz tube;
[0102] S3, vertically place the quartz tube in the corundum crucible b, and heat the whole in a pit furnace. When the temperature rises to 1010°C, the metal element melts and the temperature is kept for 48 hours;
[0103] S4, using an oscillating method, the corundum crucible b kept warm in step S3 is cooled to 920°C at 2°C / h, then heated to 990°C at 1°C / h, and finally cooled to 950°C at 1°C / h, at which time crystal nuclei are precipitated in the corundum crucible a;
[0104] S5, cooling the melt in the corundum crucible b after cooling in step S4 to 860°C at a rate of 1°C / h;
[0105] S6. Take out the quartz tube at 860°C and quench it in liquid nitrogen to obtain Mn 1.9 Ni 0.1 Sb alloy single crystal.
[0106] The Mn prepared in this example 1.9 Ni 0.1 The Sb alloy single crystal sample was ground in an agate mortar and analyzed by XRD diffraction to obtain Mn 1.9 Ni 0.1 Sb polycrystalline XRD diffraction pattern, such as Figure 4 As shown in the figure, the Mn prepared in this embodiment 1.9 Ni 0.1 The polycrystalline material after grinding the Sb alloy single crystal material is pure phase. Since the polycrystalline material is ground from the single crystal, it can be inferred that the Mn 1.9 Ni 0.1 The Sb alloy single crystal material is a tetragonal crystal.
[0107] The method for preparing Mn2Sb-based alloy single crystals by melt cooling method proposed in the present invention not only effectively avoids the problem of impurity phase when preparing Mn2Sb-based alloys in the prior art, but also prepares high-quality and large-sized Mn2Sb-based alloy single crystals. Compared with samples with impurity phases, the present invention is expected to improve the internal stress of the single crystal and enhance the overall performance and service life of the material. At the same time, due to the high quality of the crystal, the single crystal prepared based on this method can reflect the intrinsic characteristics of the system, which is helpful to further study its magnetic phase transition, topological magnetic structure and topological Hall effect and other transport problems. In addition, high-quality single crystal samples have magnetic anisotropy compared to polycrystalline samples. When they are further applied to multiple fields such as magnetic refrigeration, magnetic storage, and magnetic sensing, it is expected to further improve their related performance.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing Mn 2 Sb-based alloy single crystal method, It is characterized in that The method comprises the following steps: S1. Weighing Weigh the metal element according to the stoichiometric ratio and place it in the corundum crucible a; S2. Sealing the tube The corundum crucible a in step S1 is placed in a quartz tube, and the quartz tube is cleaned with an inert gas, evacuated, and sealed; S3. Smelting The quartz tube sealed in step S2 is placed vertically in the corundum crucible b, heated until the metal element is melted, and kept warm; S4, Oscillation cooling The corundum crucible b kept warm in the oscillation step S3 is subjected to a process of cooling-heating-cooling in sequence at a certain rate until crystal nuclei are precipitated in the melt; S5. Cooling Cooling the corundum crucible b after the temperature reduction in step S4 to a final temperature at a certain rate; S6, Quenching At the final temperature of step S5, the quartz tube is taken out and rapidly quenched to obtain Mn 2 Sb-based alloy single crystal.
2. The method according to claim 1, It is characterized in that In step S1, the purity of the metal element is not less than 99.9%.
3. The method according to claim 1, It is characterized in that In step S3, the insulation time is 24 to 48 hours.
4. The method according to claim 1, It is characterized in that In step S3, the insulation temperature is 1010°C.
5. The method according to claim 1, It is characterized in that In step S4, the oscillation times are 2 to 3 times, the cooling rate is 1°C / h to 2°C / h, the heating rate is 1°C / h to 3°C / h, and the temperature of crystal nucleation is 950°C.
6. The method according to claim 1, It is characterized in that In step S5, the cooling rate is 1°C / h to 2°C / h.
7. The method according to claim 1, It is characterized in that In step S5, the final temperature is 860°C.
8. The method according to claim 1, It is characterized in that In step S6, the quenching medium is ice water or liquid nitrogen.
9. Mn prepared by the method according to any one of claims 1 to 8 2 Sb-based alloy single crystal, It is characterized in that The Mn 2 The chemical formula of Sb-based alloy single crystal is: Mn 2-x T x Sb(Ⅰ); In formula (I), the value range of x is 0≤x≤1, and T is a transition metal.
10. Mn as claimed in claim 9 2 Application of Sb-based alloy single crystals in magnetic refrigeration, magnetic storage and magnetic sensing.
Citation Information
Cited By
Zn-doped Mn2Sb-based magnetic refrigeration material, preparation method and application thereof
CN122930717A
